Mechatronics engineering and modern information technologies in industrial engineering selected, peer reviewed papers from the 2014 International Conference on Mechatronics Engineering and Modern Technologies in Industrial Engineering (MEMTIE 2014), October 25-26, 2014, Changsha, Hunan, China - Shao, Fang; Long, Fenjie; Liang, Jie; Chen, Haihong; Yuan, Meini (Applied Mechanics and Materials, 2015)
Collection of selected, peer reviewed papers from the 2014 International Conference on Mechatronics Engineering and Modern Technologies in Industrial Engineering (MEMTIE 2014), October 25-26, 2014, Changsha, Hunan, China. The 664 papers are grouped as follows